DUAL MODALITY TOMOGRAPHY : Principles, Techniques & Applications - Jaysuman Pusppanathan,; Ruzairi Abdul Rahim,; Norhaliza Abdul Wahab,; Elmy Johana Mohamad, (2022)
There is a widespread need for the direct analysis of the internal process plants in order to improve design and operation of equipment. Process tomography involves using tomographic imaging methods to manipulate data from remote sensors in order to obtain precise quantitative information from inaccessible locations. This book discusses on Dual Modality Tomography - Principles, Techniques & Application. It’s very useful to the process engineer and researcher in this area.